2013
DOI: 10.1108/jkic-07-2013-0012
|View full text |Cite
|
Sign up to set email alerts
|

Organizational change capacity and organizational performance

Abstract: Purpose -The main purpose of this study is examining the relationship between organizational change capacity (OCC) and organizational performance (OP). Design/methodology/approach -After extensive researches in organizational literature about change and performance, the OCC model from Judge and Douglas consists of eight dimensions (trustworthy leadership, involved mid-management, capable champions, innovative culture, trusting followers, systems thinking, accountable culture, and effective communication), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
69
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(69 citation statements)
references
References 40 publications
0
69
0
Order By: Relevance
“…Organizations today are trying to adapt to all the changes surrounding them by improving their performance through the competitive advantage they create (Ramezan et al, 2013;Masa'deh et al, 2015). Researchers have always looked at organizational performance as the ultimate dependent variable concerned with almost every area in management.…”
Section: Organizational Performancementioning
confidence: 99%
See 1 more Smart Citation
“…Organizations today are trying to adapt to all the changes surrounding them by improving their performance through the competitive advantage they create (Ramezan et al, 2013;Masa'deh et al, 2015). Researchers have always looked at organizational performance as the ultimate dependent variable concerned with almost every area in management.…”
Section: Organizational Performancementioning
confidence: 99%
“…Carton (2004) suggested that organizational performance is the voluntary association of productive assets that lead to the achievement of shared purpose. Another definition of organizational performance refers to it as "the ability to acquire and process properly human, financial, and physical resources to achieve the goals of the organization" (Ramezan et al, 2013).…”
Section: Organizational Performancementioning
confidence: 99%
“…The study is novel and original for many reasons. First, few studies in the previous literature depict that there is a lack of empirical research on the notion of OCC both in the Western and Asian contexts, and relatively little is known about its antecedent conditions (Judge, 2011;Judge et al, 2015;Oxtoby, McGuiness, & Morgan, 2002;Ramezan, Sanjaghi, & Rahimian Kalateh baly, 2013;Soparnot, 2011). Second, the literature on the relationship between OCC and leadership (i.e., transformational leadership, transactional leadership, and laissez-faire leadership) lacks attention.…”
Section: Introductionmentioning
confidence: 99%
“…Judge (2011) described OCC as "a dynamic, multidimensional capability that enables an organization to upgrade or revise existing organizational competencies, while cultivating new competencies that enable the organization to survive and prosper" (p. 14). This dynamic capability is critical for all forms of organizations at some point of time (Oxtoby et al, 2002) and is associated with higher levels of organizational performance (Judge et al, 2015;Ramezan et al, 2013). OCC enables organizations to adapt and settle old capacities as well as to cope with newly emerging opportunities (Judge & Elenkov, 2005).…”
Section: Occmentioning
confidence: 99%
“…Businesses are trying to flourish and adapt to the various challenges they encounter in today's competitive environment by improving their organizational performance [1] and [2]. In order to achieve better results and higher profit margins organizations are adopting various emerging business tools and management philosophies [3].…”
Section: Introductionmentioning
confidence: 99%